In vitro and in silico protein corona formation evaluation of curcumin and capsaicin loaded-solid lipid nanoparticles. (December 2019) - Nishihira, Vivian Shinobu Kishimoto; Rubim, Alexandre Machado; Brondani, Morgana; dos Santos, Jessica Tadiello; Pohl, Ariane Ribas; Friedrich, Jadriane Fontoura; de Lara, Jéssica Dotto; Nunes, Christian Masseron; Feksa, Luciane Rosa; Simão, Eder; de Almeida Vaucher, Rodrigo; Durruthy, Michael Gonzalez; et al.
Abstract: Nanotechnology has been an important tool for the production of nanoparticles with controlled release of drugs for therapeutic applications. Here, we produced solid lipid nanoparticles (SLN) loaded with curcumin and capsaicin (NCC) following the overarching goals of green chemistry. Currently, besides evaluating the composition, and size of these, it is necessary to understand the interactions between nanoparticles and the biomolecules present in the biological medium. For this, assays were conducted in order to evaluate the potential formation of the protein 'corona', and to better understand the results obtained in vitro, we also performed an interaction study, in silico, between the NCC components and the main serum protein, albumin. In the first hour of contact between the NCC and the culture medium showed fluctuation in the diameter of the NCC. However, after 24 and 48 h of the incubation period, all NCC concentrations showed an increase in size, which can be attributed to plasma protein adsorption. Since, hard corona takes a few seconds, while the soft corona can be formed in minutes up to a few hours. On the other hand, best docking binding-poses of interaction for the formed docking complexes evaluated suggest interactions following the docking affinity like free energy FEB (Tween 80-bovine serum albumin) ≈ FEB (Span 80-bovine serum albumin) showing a pharmacodynamic pattern based in non-covalent hydrophobic interactions with the bovine serum albumin binding-site. Our in silico results clarify and reinforce our in vitro findings of corona formation, which represents the real interaction with cell membranes in vivo . Graphical abstract: Unlabelled Image Highlights: In silico study clarify and reinforce our in vitro findings of 'corona' formation. Size measurement of NCC in the cell culture complete medium showed the interaction with DMEM. FEB showed non-covalent hydrophobic interactions with the bovine serum albumin binding-site.